Assessment of clinical epidemiology, treatment patterns, and survival outcomes in epithelial ovarian cancer: a retrospective analysis from a tertiary cancer centre in North India - Sharma, Jyoti; Gupta, Manish; Thakur, Vandana; Fotedar, Vikas; Vats, Sidharth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ovarian cancer stands as the daunting third most prevalent cancer among females. The aim of this study is to assess the clinical epidemiology, treatment patterns (including end-of-life care), and survival outcomes among patients diagnosed with epithelial ovarian cancer. Methods: This retrospective analysis encompassed all patients diagnosed with epithelial ovarian cancer and enrolled at the tertiary cancer center, IGMC Shimla in Himachal Pradesh. The study included patients registered between January 2014 and December 2018, spanning all age groups. Results: During the aforementioned period, ovarian cancer accounted for 18.7% of gynaecological cancers among females out of which epithelial ovarian cancer accounted for 14.8% of the cases. The median age of patients diagnosed with epithelial ovarian cancer (EOC) was 54.5 years. Most patients hailed from Shimla, followed by Mandi and Kullu districts, among the twelve districts in the state of Himachal Pradesh. The majority of patients were diagnosed at advanced stages FIGO III and IV, comprising a total of 77.1%. Chief complaints included abdominal pain, followed by abdominal distention, heaviness, or bloating. The median duration of follow-up was 27 months (with a standard deviation of ±9.175). The median overall survival (OS) for stage I, II, III, and IV was 92.59 months, 87 months, 82.17 months, and 52.5 months, respectively, and these differences were statistically significant. Conclusions: Ovarian cancer patients are often diagnosed in advanced stages III and IV, primarily due to late diagnosis and the presence of vague symptoms. Achieving optimal cytoreduction significantly improves overall survival. Therefore, it's crucial to raise awareness among general physicians in rural healthcare settings and the public about the symptoms of ovarian cancer to facilitate early detection. Additionally, there's a notable deficiency in end-of-life discussions and palliative care management, which should be accessible to every patient.